Nanodrugs Manipulating Endoplasmic Reticulum Stress for Highly Effective Antitumor Therapy - Xiang, Yuting; Liu, Min; Yang, Yunrong; Wang, Yubo; Qiu, Yige; Tu, Shiqi; Jiang, Yitian; Nan, Yayun; Zhang, Xiaojie; Huang, Qiong (Frontiers in Pharmacology, 2022)
Cancer is one of the leading causes of death worldwide due to high morbidity and mortality. Many attempts and efforts have been devoted to fighting cancer. Owing to the significant role of the endoplasmic reticulum (ER) in cell function, inducing ER stress can be promising for cancer treatment. However, the sustained activation of cytoprotective unfolded protein response (UPR) presents a tremendous obstacle for drugs in inducing unsolved ER stress in tumor cells, especially small-molecule drugs with poor bioavailability. Therefore, many emerging nanodrugs inducing and amplifying ER stress have been developed for efficient cancer treatment. More importantly, the novel discovery of ER stress in immunogenic cell death (ICD) makes it possible to repurpose antitumor drugs for immunotherapy through nanodrug-based strategies amplifying ER stress. Therefore, this mini-review aims to provide a comprehensive summary of the latest developments of the strategies underlying nanodrugs in the treatment of cancer via manipulating ER stress. Meanwhile, the prospects of ER stress–inducing nanodrugs for cancer treatment are systematically discussed, which provide a sound platform for novel therapeutic insights and inspiration for the design of nanodrugs in treating cancer.